2003
DOI: 10.1093/milmed/168.6.457
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Malaria in a Forward Battalion on Active Service in East Timor

Abstract: An outbreak of malaria first developed within Second Battalion Royal Australian Regiment, a forward (Australian) Battalion of the International Force in East Timor in October 1999. Before the Battalion redeployed to Australia, 17 cases had occurred and in the 12 months following return to Australia another 89 cases have occurred, including 18 single recurrences and 2 second recurrences. The overall attack rate for this deployment of 4 months, mostly including the wet season of Timor, has been 13.5%. The attack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Malaria rates coincided with increased hostilities during operations, which further compromised antimalaria precautions. Similarly Kitchener et al [4], reported an outbreak of malaria in an Australian military battalion deployed in East Timor. They used similar diagnostic strategy as the present study i.e., rapid screening with ICT testing and confirmation with thick and thin blood smear examination.…”
Section: Discussionmentioning
confidence: 95%
“…Malaria rates coincided with increased hostilities during operations, which further compromised antimalaria precautions. Similarly Kitchener et al [4], reported an outbreak of malaria in an Australian military battalion deployed in East Timor. They used similar diagnostic strategy as the present study i.e., rapid screening with ICT testing and confirmation with thick and thin blood smear examination.…”
Section: Discussionmentioning
confidence: 95%
“…Malaria is known to be a significant problem for military personnel due to the high exposure risk of their activities (Porter 2006, Elmes 2010. Factors associated with malaria risk in military personnel include compliance to chemoprophylaxis and other preventive measures, side effects from medications, perception of susceptibility to mosquito bites and malaria risk, lack of preventative medicine support, involvement in night operations, location of platoon positions, and general compliance within the group (Anonymous 2001, Peragallo et al 2002, Kitchener et al 2003, Resseguier et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…chemoprophylaxis, repellent use, and proper use of impregnated uniforms) and the impossibility of performing environmental control (e.g. sanitation of potential mosquito breeding places and habitats in combat areas, including the use of impregnated bed-nets) resulted in malaria outbreaks in the US, French, Italian, Australian, British and Dutch Forces [24][25][26][27][28][29][30][31][32]. During this period, resistance to most of the drugs used in treatment of or chemoprophylaxis for both P. falciparum and P. vivax increased or emerged [33].…”
Section: Mosquito-borne Diseasesmentioning
confidence: 99%